A technological pedagogical content knowledge based instructional design model: a third version implementation study in a technology integration course - Lee, Chia-Jung; Kim, ChanMin (Educational technology research and development, 2017)
This paper presents the third version of a technological pedagogical content knowledge (TPACK) based instructional design model that incorporates the distinctive, transformative, and integrative views of TPACK into a comprehensive actionable framework. Strategies of relating TPACK domains to real-life learning experiences, role-playing, and teachers as designers were developed based on the three views and integrated into the third version of the model. The model was then applied in a teacher education undergraduate course on technology integration. A case study approach was used. Data were collected from the participants' discussion worksheets, lesson designs, and the researchers' field observation notes. Data analysis results suggest that the strategies integrated into the model helped the participants deepen their understanding of student-centered technology applications and practice TPACK. Findings, implications, and future research possibilities are discussed.